Cultivating Transcultural Understanding through Migration-related Videogames. (June 2016) - Chin, Esther; Golding, Dan
This article provides a comprehensive, worldwide overview of the major video games that have addressed the phenomenon of migration, and the political, social and cultural issues that migration raises. We develop the concept of 'transcultural understanding' to explore how such migration-related video games can structure the development of players' understanding of, and capacity to respond to, the contexts of cultural diversity. Our deeper, comparative analysis of three migration-related video games— Escape from Woomera (EFW Team, 2003), Papers, Please (Lukas Pope, 2013) and Everyday Racism (All Together Now, 2014)—enables us to evaluate the contextual knowledge required and the issues raised for each migration-related video game to achieve its goals. This article advances the research areas of 'media, migration and global communication' and 'games studies', and offers insights for scholars, educators and game developers who are interested in addressing the internationally significant issue of migration through their professional work.